Dicephalic parapagus twin - A rare case report - Singh, Richa; Rattan, Kamal; Sonika, Pallavi (Indian Journal of Child Health, 2017)
We are reporting a rare case of a dicephalic parapagus twin born to multigravida mother diagnosed antenatally few hours before birth by ultrasonography. The baby was born by emergency cesarean section. The baby was full-term live male baby; however, the baby expired few hours after birth. Due to the rarity of the case, we are prompted to report this case.